(untitled) (Nusantara Medical Science Journal, 2023)
Introduction: The survival rate of cancer patients was high due to chemotherapy, but it can cause cardiotoxicity and increase morbidity and mortality. Most studies on cancer therapy-related cardiac dysfunction (CTRCD) focus more on the left ventricle. This study assesses chemotherapy’s effect on the right ventricle, namely the right ventricle free wall longitudinal strain (RVFWLS). Methods: This study is a prospective cohort conducted from January to December 2022 on thirty-four cancer patients undergoing chemotherapy at Dr Wahidin Sudirohusodo Hospital Makassar. The RVFWLS was assessed before and after chemotherapy using echocardiographic. Result: The RVFWLS value after one cycle chemotherapy decreased compared pre-chemotherapy (4.40±4.84; p=0.001). Conclusion: The effect of chemotherapy is a decrease the RVFWLS value after the first cycle of chemotherapy. It should be considered for echocardiographic evaluation, especially the RVFWLS value every cycle of chemotherapy.